Incidence, Causes and Management of Retained Placenta of Admitted Cases in In-Patient Department of Dhaka Medical College Hospital - Das, SR; Sultana, N; Akhter, S; Khan, F; Wazed, F (Journal of Dhaka Medical College, 2010)
Retained placenta is a condition in which the placenta is retained for more than half-an hour after the birth of a child. It accounts for 5-10% of all postpartum haemorrhage (PPH). The present study was conducted to find out the incidence, causes and management of retained placenta of admitted cases in In-Patient Department (IPD) of Obstetrics & Gynaecology of Dhaka Medical College Hospital, Dhaka during the period from June 01 to December 31, 2003. 163 patients were included in the study who presented with retained placenta and developed retained placenta in IPD who had undergone vaginal delivery, with pregnancy equal to or more than 28 weeks both stillbirths and live-births, both singleton and multiple pregnancy. The incidence of retained placenta was found 3.54% of total admissions. Retained placenta developed in 1.53% cases among 1,506 vaginal deliveries in this hospital during this period. The mean age of the respondents was 27.19±1.54 and most of the patients were aged between 21 to 30 years, multipara, illiterate and from low income group and poor socio-economic status. Among them 81.60% had home delivery, 64.42% delivered between 37 to 40 weeks of pregnancy. Majority of the patients i.e. 61.96% reached the hospital within 2 to 6 hours of development of retained placenta and 49.07% had shock with PPH. About 23.92% respondents had predisposing factors like D & C, manual removal of RP and caesarean section. A considerable percentage (19.63%) had history of MR. About 96.93% respondents required manual removal of retained placenta. 124 (76.07%) received blood transfusion ranging from 1 to 13 units of blood. The causes of retained placenta were uterine inertia (38.65%), morbid adhesion (52.76%) and less expulsive efforts of the patients (7.98%). Placenta accreta was the major (96.51%) cause of morbid adhesion. The range of hospital stay was between 6 to 15 days. Of the total retained placenta cases, 98.77% patients improved and 1.23% patients died of irreversible shock due to PPH. Key words: Retained Placenta; Caesarean Section. DOI: 10.3329/jdmc.v18i1.6300 J Dhaka Med Coll. 2009; 18(1) : 20-24